Pengaruh Perilaku Asertif Staf Perpustakaan Terhadap Kualitas Pelayanan di Dinas Perpustakaan dan Arsip Kabupaten Karo - Darmayanti, Lisa; Batubara, Abdul Karim; Purwaningtyas, Franindya (Prodi Ilmu Perpustakaan dan Informasi Universitas Islam Negeri Raden Fatah Palembang, 2024)
The assertive behavior of library staff toward service quality in the archives and library of the Karo Regency is discussed in this thesis. The purpose of this study is to determine how the assertive behavior of library employees affects the level of customer service provided by the Karo Regency library and archives. This study employs a comparative causal approach with quantitative methodologies. through the use of methods for gathering data, such as surveys and recordkeeping. The Karo Regency library and archives service workers served as the research's informants. The study's findings indicate that library employees' assertive behavior improves the quality of their services. The acceptance of Ha is based on the demonstrable assertive behavior (X) towards service quality (Y) with a significant value of 0.000 > 0.05.